Implementing Western musical notation in teaching Sundanese titilaras: Qualitative action research - Supriatna, Nanang; Sukmayadi, Yudi; Gunawan, Iwan (LPMPP Universitas Negeri Yogyakarta, 2025)
Music education promotes students' cultural and intellectual development, particularly in preserving traditional music. Sundanese traditional music in Indonesia, mainly through the concept of titilaras, encapsulates cultural identity and history. Modern music education encounters a hurdle as Western musical notation predominates courses, resulting in students needing help comprehending and performing Sundanese music due to the disparities in notation systems. This research examined the imperative of safeguarding Sundanese titilaras by investigating the incorporation of Western musical notation in its pedagogy to improve students' proficiency in reading and composing traditional Sundanese music. The research utilized a qualitative action research technique at Indonesian University of Education, engaging 48 students from various cultural origins and different levels of music education. The research evaluated students' skills in titilaras before and after integrating Western notation through surveys, aural assessments, and music transcription activities. The findings revealed that most pupils encountered difficulties with Sundanese musical notation while demonstrating proficiency in Western notation. Utilizing Western musical notation as an instructional instrument, students exhibited enhanced comprehension and execution of Sundanese scales, particularly in practical contexts such as transcription and melody interpretation. The study indicated that integrating Western notation into the curriculum could enhance accessibility to traditional music for students acquainted with Western systems. Thus, Sundanese music maintained its cultural integrity while fulfilling modern educational requirements. This research underscored the necessity of modifying music education to preserve local musical traditions within an increasingly international framework.